2016
DOI: 10.1111/ajt.13617
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Infiltrates in Operational Tolerant Patients After Liver Transplantation Show Enrichment of Regulatory T Cells Before Proinflammatory Genes Are Downregulated

Abstract: These authors contributed equally as a senior author. ‡ Equal first authors.Immunosuppression can be discontinued from selected and stable patients after liver transplantation resulting in spontaneous operational tolerance (SOT), although the underlying mechanisms remain elusive. Thus, we analyzed serial liver biopsy specimens from adult liver recipients enrolled in a prospective multicenter immunosuppression withdrawal trial that used immunophenotyping and transcriptional profiling. Liver specimens were colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
54
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 30 publications
13
54
1
1
Order By: Relevance
“…Operational tolerance is a rare phenomenon after LT [18]. Tregs have been proposed to be key in strategies aiming for tolerance and immunomodulation after SOT [35]. In a recent paper, Todo et al demonstrated that a single Treg injection might promote operational tolerance after living-related LT [36].…”
Section: Discussionmentioning
confidence: 99%
“…Operational tolerance is a rare phenomenon after LT [18]. Tregs have been proposed to be key in strategies aiming for tolerance and immunomodulation after SOT [35]. In a recent paper, Todo et al demonstrated that a single Treg injection might promote operational tolerance after living-related LT [36].…”
Section: Discussionmentioning
confidence: 99%
“…This is very interesting and somehow unexpected, especially in relation to findings from other IS weaning trials, but in accordance with previous observations in preclinical models. In contrast to the findings presented by Taubert et al (4), increase in portal tract infiltration has rarely been observed; however, most of the published data came from weaning trials with pediatric liver transplant patients (5). In addition, the presence of Foxp3 + T cells in graft infiltrates is controversial because it may enhance fibrosis development at later time points and has been associated with development of chronic rejection.…”
Section: Foxp3mentioning
confidence: 90%
“…In this issue of the American Journal of Transplantation, Taubert et al (4) have engaged this matter and studied the sequence and phenotype of infiltrating leukocytes following IS withdrawal in patients with OT (5). Apart from quantifying the changes of total portal tract infiltrate, Taubert et al concentrated on the balance of Foxp3 + regulatory and Foxp3…”
Section: Foxp3mentioning
confidence: 99%
See 1 more Smart Citation
“…Some immunosuppressive regimens might also affect effector cells, and in that way facilitate tolerance induction. Therefore, it remains unknown whether Treg are mandatory in OT following LT. Several groups are working on identifying biomarkers of tolerance that would help the clinician detecting tolerant individuals [7] or clinical complications such as recurrent hepatitis C [19][20][21]. Most studies have utilized peripheral blood mononuclear cells, but liver samples may be more relevant to identify such markers [19,22].…”
mentioning
confidence: 99%